1982
DOI: 10.1177/001112878202800104
|View full text |Cite
|
Sign up to set email alerts
|

Conjugal Association in Prison: Issues and Perspectives

Abstract: The practice of conjugal association in United States prisons has be come a controversial issue among policy makers in correction. Seven states now have programs allowing families to visit inmates in private, and to engage in sexual activity with their spouses on prison grounds. This paper describes conjugal association programs now operating in United States prisons and reviews the long debate in the literature over the merits of such programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
2

Year Published

1984
1984
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 1 publication
1
7
0
2
Order By: Relevance
“…The findings of this study correlate with other research findings revealing that conjugal visits decrease the emotional frustrations of inmates (Goetting, 1982), reduce tension among inmates (Chesney-Lind & Pollock-Byrne, 1995;Wyatt, 2005), and foster dyadic stability (Carlson & Cervera, 1991;Owen, 1998;Pollock-Byrne, 1990;Robertson, 1999). The participants of this study maintained that the visits with their spouses allow them to disclose their personal anxieties and sorrows, receive valuable emotional support, and make plans for the future with their partners.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The findings of this study correlate with other research findings revealing that conjugal visits decrease the emotional frustrations of inmates (Goetting, 1982), reduce tension among inmates (Chesney-Lind & Pollock-Byrne, 1995;Wyatt, 2005), and foster dyadic stability (Carlson & Cervera, 1991;Owen, 1998;Pollock-Byrne, 1990;Robertson, 1999). The participants of this study maintained that the visits with their spouses allow them to disclose their personal anxieties and sorrows, receive valuable emotional support, and make plans for the future with their partners.…”
Section: Discussionsupporting
confidence: 89%
“…Conjugal visits are believed to have positive effects during and after confinement (Hensley, Rutland, & Gray-Ray, 2000b;Tewksbury & DeMichele, 2005): namely, the reduction of sexual and nonsexual violence among inmates and the provision of opportunities to preserve family ties and marital stability (Turner, 2000). Nonetheless, only a few studies have made a theoretical and empirical attempt to address these issues in men's prisons (Bennett, 1989;Goetting, 1982;Wyatt, 2005), and fewer studies dealt with these issues in women's prisons (Hensley et al, 2000b;Hensley, Rutland, Gray-Ray, & Durant, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The term, "red houses" actually came from the paint used on the outside walls rather than a reference to the "red light district." Official recognition of the conjugal visitation program did not begin until 1965 when the first brick "red house" was constructed (Goetting, 1982;Hopper, 1969). In 1972, the prison administration at Parchman began to support the program; thus, allowing female inmates to participate (Hopper, 1989).…”
Section: Conjugal Visitation Programs In Correctional Facilitiesmentioning
confidence: 99%
“…Using these variables, Morris constructed a typology with eight situations predicting whether marital relationships would be strained or strengthened by a husband's imprisonment, and she made specific recommendations for the "treatment of family problems as a whole" by prison and social services (Morris 1965, p. 10). Yet rather than inspiring derived studies, development of her analytical framework, or implementation of her suggested policy reforms, Morris's substantial contribution lay essentially untouched by the sparse and conceptually isolated publications of the next three decades, which appeared chiefly in psychology, social work, criminology, and corrections (see, for example, Gibbs 1971, Sack et al 1976, Bakker et al 1978, Daniel & Barrett 1981, Goetting 1982, Hinds 1982, Hannon et al 1984, Lowenstein 1986.…”
Section: Introductionmentioning
confidence: 99%